Akuntansi berbasis website melalui aplikasi Dac Easy Accounting (DEA) dalam meningkatkan minat belajar mahasiswa - Marlina, Siska; Ariesti Anggraeni, Windi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Educational models of accounting practices in higher education have been introduced, but there are still many obstacles in the use of accounting software. An application that can assist students in operating the accounting process, especially in preparing financial statements using formulas in a computerized system, is Dac Easy Accounting (DEA). Given the upcoming economic challenges, students need to master information technology, which is an important tool in their careers in the field. This study aims to analyze Website-Based Accounting through the DEA application program in increasing student interest in learning in Garut Regency. The research method used is descriptive comparative, with the aim of describing the facts and relationships that exist. The results showed that there are factors that can increase students' interest in learning and practicing DEA applications in accounting. Internal factors include motivation, interest, and encouragement of competition in the world of work. While external factors involve the role of family, facilities, and environment. To support students' understanding, adequate learning facilities are needed, as well as professional and experienced teachers.